Penerapan Platform Informasi Pelayanan Data Terpadu Kesejahteraan Sosial (DTKS) - Lusi Ariyani; Achmad Sarwandianto (Jurnal Kabar Masyarakat, 2025)
According to Article 11 Paragraph 2 of Law number 13 of 2011 concerning Handling of the Poor, the government and regional governments can provide assistance and/or empowerment based on integrated data that has been created by the minister. DTKS is household based, but the poverty alleviation program uses social assistance and community empowerment based on families and individuals. The Family Hope Program (PKH) and Social Food Assistance are examples of family-based social assistance and community empowerment. Regional governments face several problems with population administration which is still carried out manually, using population registers, and local people are not aware of the poor administration system and do not report it. If population data changes. Therefore, it is necessary to apply information technology to certain areas in managing population administration, which is very important considering the population continues to grow.